Gender agreement hierarchy in common gender and epicene nouns in Spanish - Ogneva, Anastasiia (Borealis – An International Journal of Hispanic Linguistics, 2020)
Gender is a grammatical category defined as an abstract morphosyntactic feature of nouns reflected in characteristics of associated words (i.e. agreement) (Hockett, 1958; Corbett, 1991). Agreement is, in fact, easily established in “transparent” nouns which follow either semantic or formal rule of gender agreement. However, when we deal with ambiguous nouns regarding their gender, agreement is not straightforward. In this article we aim to pursue two main goals. Firstly, to review and briefly describe grammatical gender system in Spanish (§1) with a special focus on so called “ambiguous” or “problematic” nouns (§2). Secondly, to review agreement hierarchy theories and explore if they are applicable for Spanish epicenes and common gender nouns (§3). Discussion and conclusion remarks are presented in (§4).